Influence of different approaches for calculating the athlete's mechanical energy on energetic parameters in the pole vault - Schade, F.; Arampatzis, A.; Brüggemann, G. P. (Journal of Biomechanics, 2000)
The purposes of this study were as follows: (1) To determine the differences between two- and three-dimensionally calculated energy of the athlete in the pole vault. (2) To determine the differences between CM energy and total body energy. (3) To examine the influence of these different approaches of calculating the athlete's energy on energetic parameter values during the pole vault. Kinematic data were gathered during the pole vault final of the track and field world championships in 1997. Two video cameras (50 Hz) covered the last step of the approach including the pole plant and 2 cameras covered the pole phase up to bar clearance, respectively. Twenty successful jumps were analysed. The characteristics of the energy development is similar for the different approaches. Initial energy, energy at maximum pole bend and energy at pole release (primary parameters) show significant differences (p<0.05). The findings indicate that rotatory movements and movements relative to the CM have a larger influence on the primary parameters than movements apart from the main plane of movement. For analysing the energy exchange between the athlete and the elastic implement pole only the differences among the secondary parameters (initial energy minus energy at maximum pole bend, final energy minus energy at maximum pole bend) are needed (Arampatzis et al., 1997 Biomechanical Research Project at the Vth World Championships in Athletics, Athens 1997: Preliminary Report. New Studies in Athletics 13, 66-69). For those parameters the relative differences between the calculation approaches range only between 1.47 and 0.04%. This indicates that the influence of the different approaches for calculating the athlete's energy on the analysis of energy exchange is negligible.